1993
DOI: 10.1111/j.1748-1716.1993.tb09489.x
|View full text |Cite
|
Sign up to set email alerts
|

A search for arteriovenous anastomoses in human skin using ultrasound Doppler

Abstract: The possible existence of arteriovenous anastomoses (AVAs) in skin regions of the head and thorax has been investigated using the synchronous vasomotion of the AVAs. Simultaneous pairs of blood velocity recordings were made using pulsed, bidirectional Doppler ultrasound. In each pair of registrations, blood velocity was recorded in a reference artery supplying a skin area known to contain AVAs (the radial artery) together with one of four other arteries investigated, i.e. the facial artery, the angular artery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 11 publications
3
61
0
Order By: Relevance
“…Bergersen (1993), for example, found that AVAs are not present in the skin of the forehead, whereas they are present in the nose. This would explain why the nose skin temperature would increase before the forehead skin temperature, in response to an increase in body heat content.…”
Section: Discussionmentioning
confidence: 95%
“…Bergersen (1993), for example, found that AVAs are not present in the skin of the forehead, whereas they are present in the nose. This would explain why the nose skin temperature would increase before the forehead skin temperature, in response to an increase in body heat content.…”
Section: Discussionmentioning
confidence: 95%
“…17 The distal skin regions of the body (hands and feet) are the major sites for vasomotor heat loss, whereas the proximal skin regions (arms, trunk, and legs) play a lesser role in thermoregulation. 18 Distal vasodilation involves arteriovenous anastomoses that are particularly abundant in the hands and feet 19 and can shunt blood directly from arterioles to veins. According to Guyton,20 "the rate of blood flow into this venous plexus can vary tremendously-from barely above zero to as great as 30 per cent of the total cardiac output.…”
Section: Electrons As Antioxidants 957mentioning
confidence: 99%
“…30 The advantages of using the temporal artery (TA) region include its proximity to the skin surface and stability of its blood flow because of its relatively constant perfusion. 31 In the pediatric ED, the TA thermometer has been found to be both more accurate than the tympanic thermometer and better tolerated than the rectal thermometer. 28 Furthermore, the fever measured by the TA device appears to defervesce more than the rectal fever, both at 60 and 90 minutes following antipyretic therapy.…”
mentioning
confidence: 99%